2018
DOI: 10.1111/pce.13152
|View full text |Cite
|
Sign up to set email alerts
|

Moisture‐driven xylogenesis in Pinus ponderosa from a Mojave Desert mountain reveals high phenological plasticity

Abstract: Future seasonal dynamics of wood formation in hyperarid environments are still unclear. Although temperature-driven extension of the growing season and increased forest productivity are expected for boreal and temperate biomes under global warming, a similar trend remains questionable in water-limited regions. We monitored cambial activity in a montane stand of ponderosa pine (Pinus ponderosa) from the Mojave Desert for 2 consecutive years (2015-2016) showing opposite-sign anomalies between warm- and cold-seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 81 publications
5
63
0
Order By: Relevance
“…Xylem water (sap) transport is also used to replace lost water from transpiration and thus is strongly connected to the photosynthesis process. The phloem is the other transport tissue which brings carbohydrates downward in the plant from the leaf source to its sinks (Sala et al 2010, Nikinmaa et al 2013, Rathgeber et al 2016, Castagneri et al 2017, Ziaco et al 2018. Both xylem and phloem interact through changes in osmotic pressure and water potential, regulating the water and carbohydrate transports in the plant (Botha 2005, Cochard et al 2009, Holtta et al 2009, Rosner et al 2018, Sevanto et al 2018, as well as turgor.…”
Section: Soil Moisture Effects On Water-carbon Couplingmentioning
confidence: 99%
“…Xylem water (sap) transport is also used to replace lost water from transpiration and thus is strongly connected to the photosynthesis process. The phloem is the other transport tissue which brings carbohydrates downward in the plant from the leaf source to its sinks (Sala et al 2010, Nikinmaa et al 2013, Rathgeber et al 2016, Castagneri et al 2017, Ziaco et al 2018. Both xylem and phloem interact through changes in osmotic pressure and water potential, regulating the water and carbohydrate transports in the plant (Botha 2005, Cochard et al 2009, Holtta et al 2009, Rosner et al 2018, Sevanto et al 2018, as well as turgor.…”
Section: Soil Moisture Effects On Water-carbon Couplingmentioning
confidence: 99%
“…The adjustment of xylogenesis to environmental conditions can be achieved by adjusting the timings or the rates of cell production (Lupi et al, 2010). Earlier starts of cambial activity have been reported in response to warmer temperatures (Lenz et al, 2013;Vieira et al, 2014a) or to water availability in hyper-arid regions (Ziaco et al, 2018;Ren et al, 2019). However, most studies have reported that growth rates rather than timings determine xylem production Ren et al, 2019).…”
Section: Timings and Kinetics Of Xylem Formationmentioning
confidence: 99%
“…Localized heating of the stem during winter and spring induced earlier cambial reactivation, confirming the role of temperature in the onset of cambial activity [7,12,13]. In the above studies, snowmelt or rainfall during early spring was sufficient to provide adequate water supply for the trees; however, other studies conducted in arid regions of the northeastern Tibetan Plateau and western United States demonstrated that moisture availability could be an important, although overlooked, factor triggering the onset of wood formation [14,15]. Water availability influences a number of physiological processes, such as cell expansion and division, by affecting the turgor pressure within cambial and derivative cells [16], which may alter the timing and duration of the cell enlargement phase as well as the final number and characteristics of tracheids [15,17].…”
Section: Introductionmentioning
confidence: 59%